Implementation Of Islamic Counseling Teachers At Tahfiz Al-Husna Islamic Boarding School High Club City - Saiful Akhyar Lubis; Usiono Usiono; Abdul Rahmad Harahap (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
The background of this research to find out how do the teachers analyze in counseling at tahfidz al-Husna boarding school in Tebing tinggi city started at the activities, authorizing in controlling to do the activities, the aspect of activities to evaluation. This research to find out the (1) the teacher’s supervisor activities in counseling and advising of Islam (2) the involvement (3) what are activities be done and (4) evaluation. This research used the qualitative method, place and time of research was at tahfidz al-Husna Boarding Schoo in Tebing tinggi city. The time for research was started on February, 2021 to July,2021. The data collecting technique was taken the interview, observation and documentation. The data collecting analysis used the data reduction, data supplying, and data conclusion. The result of research found out: (1) the teacher’s supervisor in applying of counseling was planned and programmed by four aspects, those are used the four closings, such as the student’s need, determined the destination on supplying of counseling, interpreted and determined subject matter based on the gender, technique, and strategy. Fund rising and facilities on supplying of counseling (2) the involvement in supplying of counseling activities done at four aspects, those are determined the counselor or teacher of tahfidz and the teacher’s boarding school advisor in group tuition in competence. Socialization on counseling supplying. The daily task description (job description) and make the partnership with stakeholder (3) activity aspect was done in several methods those are the right model method, persuasion method and story method (4) the evaluation was coming of background by the obstacle. For the obstacle was divided into two parts, those the inclusive and exclusive. For the inclusive is less of optimal on time for doing the counseling supplying activity. The less of attention of supervising from the head leader of institution into the field. For the obstacle of exclusive because less of the facility optimal according to supplying construction of counseling from the expert of counselor, the less optimal from the high attention such as the ministerial religion affairs branch of Tebing tinggi, the less of head leader’s attention and the header’s attention of institution. The evaluation gave 6 monthly one and the less optimal of counseling supplying training.